Size‐tailored synthesis and luminescent properties of three‐dimensional BaMoO4, BaMoO4:Eu3+ micron‐octahedrons and micron‐flowers via sonochemical route. (26th June 2014) - Zhang, Junjun; Li, Linlin; Zi, Wenwen; Zou, Lianchun; Gan, Shucai; Ji, Guijuan
Abstract Almost monodisperse three‐dimensional (3D) BaMoO4, BaMoO4:Eu3+ micron‐octahedrons and micron‐flowers were successfully prepared via a large‐scale and facile sonochemical route without using any catalysts or templates. X‐Ray diffraction (XRD), field emission scanning electron microscopy (FE‐SEM), energy dispersion X‐ray (EDS), Fourier transform infrared (FTIR) and photoluminescence (PL) spectroscopy were employed to characterize the as‐obtained products. It was found that size modulation could be easily realized by changing the concentrations of reactants and the pH value of precursors. The formation mechanism for micron‐octahedrons and micron‐flowers was proposed on the basis of time‐dependent experiments. Using excitation wavelengths of 396 or 466 nm for BaMoO4:Eu3+ phosphors, an intense emission line at 614 nm was observed. These phosphors might be promising components with possible application in the fields of near UV‐ and blue‐excited white light‐emitting diodes. Simultaneously, this novel and efficient pathway could open new opportunities for further investigating the properties of molybdate materials. Copyright © 2014 John Wiley & Sons, Ltd.